2021
DOI: 10.1097/ijg.0000000000001799
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Clinical Outcomes of Acute Primary Angle Closure Randomized to Receive Early Phacoemulsification Versus Laser Peripheral Iridotomy

Abstract: Purpose: To compare the 10-year clinical outcomes of eyes with acute primary angle closure (APAC) randomized to receive either early phacoemulsification or laser peripheral iridotomy (LPI). Methods: Sixty-two APAC patients, who underwent either early phacoemulsification (phaco group) or laser peripheral iridotomy (LPI group) in a previous randomized controlled trial, were invited for assessment 10 years after the interventions. The results of the 2 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…In a more recent follow‐up study of the same cohort, they found that patients undergoing clear‐lens extraction were 10 times more likely to achieve good IOP control postoperatively without the need for topical therapy or surgery for up to 3 years 32 . Although the role of lens extraction as a primary treatment might still be questionable, especially in younger patients who can still accommodate and those with modestly raised IOP, it seems that early lens extraction is beneficial in terms of improved patient‐reported quality of life, better IOP control, and reduced need for glaucoma medication for patients who experienced an episode of APAC 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…In a more recent follow‐up study of the same cohort, they found that patients undergoing clear‐lens extraction were 10 times more likely to achieve good IOP control postoperatively without the need for topical therapy or surgery for up to 3 years 32 . Although the role of lens extraction as a primary treatment might still be questionable, especially in younger patients who can still accommodate and those with modestly raised IOP, it seems that early lens extraction is beneficial in terms of improved patient‐reported quality of life, better IOP control, and reduced need for glaucoma medication for patients who experienced an episode of APAC 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…55 There are many studies devoted to the advantages of LE over LPI in acute primary closed angle. 56,57 The insufficiency of LPI for the treatment of acute primary closed angle is proven by the fact that 30% of patients subsequently require trabeculectomy due to IOP decompensation. 58 In addition, late LE due to the formation of goniosynechia in the eyes that had previously undergone trabeculectomy 59 or LPI in subsequent selective laser trabeculoplasty 60 does not lead to a decrease in ITC.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 36 PACG patients were followed up for more than two years after LE, and 69.4% of these patients showed progression in optic nerve damage [23]. Moreover, Chan et al [24] evaluated 19 patients with acute primary angle closure who underwent early phacoemulsi cation after 10 years and found that these patients had a mean anterior synechiae range of 120.0°±116.12. We speculate that this discrepancy may relate to different mechanisms of angle-closure.…”
Section: Discussionmentioning
confidence: 99%